Development of modified ceramic membranes by silica dip-coating method for removal of co2 from biogas plant - Mohd Daud, Farah Diana; Mel, Maizirwan; Ahmad Azhar, Ahmad Zahirani (2018)
Biogas energy conversion is a new technique that have been develop for effective and proper utilization of renewable energy. Methane (CH4) and carbon dioxide (CO2) are the major component of the biogas. Therefore, the CO2 must be removed in order to increase the energy conversion. In this research, silica ceramic membrane separation method was applied to remove CO2 from the biogas. Tetraethyl orthosilicate (TEOS), ethanol, distilled water and acid was used as a solution for membrane fabrication by using sol-gel dip-coating method. There are several parameters are varied during the preparation of silica ceramic membranes, including amount of acid, molar ratio of water, number of dipping and calcination temperature. Using commercial alumina ceramic as the substrate or support, the support was dipped into the prepared solution. The fabricated membranes were dried for 24 hours at room temperature and then heat treated. The fabricated silica ceramic membranes were tested for carbon dioxide removal, by using permeation test method. Inlet and outlet pressure of the permeation test were varied. The membranes are then characterized using X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Field Emission Electron Microscopy (FESEM) and Scanning Electron Microscope (SEM). From the XRD analysis, the fabricated silica ceramic membrane showed the existence of silicate hydrate in the final product. FESEM images indicated that the silica ceramic membrane has been deposited on the tubular ceramic support as a substrate and penetrate into the pore walls. The IR adsorption from FTIR indicates the presence of functional group O-Si-O and Si-CH3. The intensity peak of FTIR decreased with increasing of amount of acids. Hence, the 8 ml of acid has demonstrated the appropriate amount of catalyst in fabricating good physical and chemical characteristic of silica ceramic membrane.The intensity of these functional groups increases as the dipping time increased. FESEM results show that the number of visible pores on the surface of the ceramic support diminished after modification of ceramic membrane, with the number of silica particles increasing linearly with number of dipping. For XRD results, the fabricated silica ceramic membrane shows the existence of silicate hydrate when calcined at 400 °C, 500 °C and 600 °C. The XRD analysis showed the highest peak intensity at 22.5° which proved the presence of silica. From the FESEM images, the pore size of the ceramic support was around 0.5 to 0.6 μm. After the silica ceramic membranes were fabricated, the pore size no longer visible under the FESEM proves that the pore size of the membranes was reduced. FTIR showed adsorption spectra of the fabricated membranes with different calcination temperature which have broad band in the region around 1060 to 1090 cm-1 correspond to the O-Si-O bond of mesoporous silica altogether confirming the existence of silica. Based on the result analysis, the suitable calcination temperature at 500 °C with less crack and more consolidated surface membrane. Thus, the synthesized silica ceramic membrane with good structure and chemical properties has shown great potential for biogas separation application.